Nasal plasmacytoma: a rare cause of persistent epistaxis. Issue 6 (18th August 2018) - Ishtiaq, Rizwan; Sarma, Kalika; Uzoaru, Ike; Khaliq, Waseem
ABSTRACT: Extramedullary plasmacytoma (EP) is a rare neoplasm characterized by monoclonal proliferation of plasma cells without features of multiple myeloma. EP constitutes 3% of all plasma cell tumors. Most of the cases of EP occur in the head and neck regions, especially in the aerodigestive tract. We present a case of recurrent epistaxis for 6 months and extensive workup revealed EP of the right nasal cavity. Primary care physicians and otolaryngologists should be aware of this very rare but a plausible cause of epistaxis and keep EP in the differential diagnosis of recurrent epistaxis.